Peran Penting Sarana dan Prasarana Dalam Keberhasilan Pembelajaran Sekolah Dasar Islam Terpadu - Miswar, Miswar; Hasibuan, Adil Rosyadi; Hutapea, Paisal Rahman; Ge’e, Ros Suryaningsih (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study aims to analyze the important role of facilities and infrastructure in the success of learning at the Integrated Islamic Elementary School (SD IT) Al Hijrah 2. The background of this study departs from the view that educational facilities and infrastructure are strategic factors that influence the effectiveness of the teaching and learning process and the achievement of integrated Islamic education goals that combine academic, spiritual, and character aspects. This study uses a qualitative method with a descriptive approach, where data is obtained through observation, interview, and documentation techniques with the principal, teachers, administrative staff, and students at SD IT Al Hijrah 2. The results of the study show that SD IT Al Hijrah 2 has facilities and infrastructure that are relatively complete and in accordance with the standards of Permendikbudristek Number 22 of 2023, including comfortable study rooms, laboratories, libraries, teacher rooms, mosques, UKS rooms, as well as sports and play facilities. The use of learning media such as globes, mannequins, and infocus also helps teachers create interactive and enjoyable learning. Complete facilities and a clean environment increase student motivation, comfort, and learning achievement. Overall, this study concludes that facilities and infrastructure are not merely physical support elements, but also fundamental components in realizing effective and meaningful learning. Good facility management contributes to improving educational quality, fostering Islamic character, and fostering a positive school image in the community.